x=4+y; x=4+y; x=4+y; x=4+y; x=4+y; y=0;
(4+y)+2(4+y)y+y^2=4; 4+y+8y+2y^2+y^2=4; 3y^2+9y=0; 3y(y+3)=0; y=0; x=4;
y=-3; y=-3;
x=1.
Выражение: 2*(X+Y)=5+X
ответ: X+2*Y-5=0
Решаем по действиям:
1. 2*(X+Y)=2*X+2*Y
2. 2*X-X=1*X
Решаем по шагам:
1. 2*X+2*Y-5-X=0
1.1. 2*(X+Y)=2*X+2*Y
2. X+2*Y-5=0
2.1. 2*X-X=1*X
Решаем уравнение X+2*Y-5=0:
Решаем относительно Y:
Y=(-X+5)/2=-X/2+5/2=-X/2+2.5.
Выражение: 3*(X+Y)+4*(5+Y)=-(X+Y+1)
ответ: 4*X+8*Y+21=0
Решаем по действиям:
1. 3*(X+Y)=3*X+3*Y
2. 4*(5+Y)=20+4*Y
3. 3*Y+4*Y=7*Y
4. 3*X+X=4*X
5. 7*Y+Y=8*Y
6. 20+1=21
Решаем уравнение 4*X+8*Y+21=0:
Решаем относительно Y:
Y=(-4*X-21)/8=-4*X/8-21/8=-0.5*X-21/8=-0.5*X-2.625.
f '(x) = 3/(2* корень(3х+2)) +4x^3